Inhibition of GABAergic Neurons and Excitation of Glutamatergic Neurons in the Ventrolateral Periaqueductal Gray Participate in Electroacupuncture Analgesia Mediated by Cannabinoid Receptor - Zhu, He; Xiang, Hong-Chun; Li, Hong-Ping; Lin, Li-Xue; Hu, Xue-Fei; Zhang, Hong; Meng, Wang-Yang; Liu, Lu; Chen, Chao; Shu, Yang; Zhang, Ru-Yue; Zhang, Pei; et al. (Frontiers in Neuroscience, 2019)
Although electroacupuncture (EA) has become a worldwide practice, little is understood about its precise target in the central nervous system and the cell type-specific analgesia mechanism. In the present study, we found that EA has significant antinociceptive effects both in inflammatory and neuropathic pain models. Chemogenetic inhibition of GABAergic neurons in the ventrolateral periaqueductal gray (vlPAG) replicated the effects of EA, whereas the combination of chemogenetic activation of GABAergic neurons and chemogenetic inhibition of glutamatergic neurons in the vlPAG was needed to reverse the effects of EA. Specifically knocking out CB1 receptors on GABAergic neurons in the vlPAG abolished the EA effect on pain hypersensitivity, while specifically knocking out CB1 receptors on glutamatergic neurons attenuated only a small portion of the EA effect. EA synchronously inhibits GABAergic neurons and activates glutamatergic neurons in the vlPAG through CB1 receptors to produce EA-induced analgesia. The CB1 receptors on GABAergic neurons localized in the vlPAG was the basis of the EA effect on pain hypersensitivity. This study provides new experimental evidence that EA can bidirectionally regulate GABAergic neurons and glutamatergic neurons via the CB1 receptors of the vlPAG to produce analgesia effects.